Effects of Exercise on Depression and Anxiety in Lung Cancer Survivors: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Cuiqing Zhao; Xifeng Tao; Bingkai Lei; Yifan Zhang; Gen Li; Yuanyuan Lv; Laikang Yu (Current Oncology, 2025)
This study aims to investigate the effects of exercise on depression and anxiety in lung cancer survivors and identify the optimal exercise prescription for this population. Searches were conducted in PubMed, Web of Science, Cochrane Library, Embase, Scopus, CNKI, and Wanfang Data up to 7 January 2024. A meta-analysis was performed to calculate the standardized mean difference (SMD) and 95% confidence interval. Thirteen studies were included in this meta-analysis. Exercise significantly alleviated depression (SMD, −0.54; p = 0.002) and anxiety (SMD, −0.66; p = 0.0002) in lung cancer survivors. Subgroup analyses showed that aerobic exercise, exercise conducted >3 times per week, <60 min per session, and ≥180 min per week, were more effective in alleviating depression and anxiety, particularly in middle-aged individuals. In conclusion, exercise alleviates depression and anxiety in lung cancer survivors, particularly those who are middle-aged, and aerobic exercise may be the most effective intervention. This meta-analysis provides clinicians with evidence to recommend that lung cancer survivors engage in exercise more than three times per week, with each session lasting less than 60 min, aiming to achieve a total of 180 min per week by increasing the frequency of exercise.